Study on Dimensional Stability of Particleboard Made Using Glutardialdehyde Modified Corn Starch as the Binder at Various Relative Humidity - Hazim Mohamad Amini, Mohd; Hashim, Rokiah; Syuhada Sulaiman, Nurul; Mohamed, Mazlan; Najmi Masri, Mohmad; Ahmad Sobri, Sharizal; Izaida Ibrahim, Nor (International Journal of Engineering and Technology, 2018)
The objective of the study was to evaluate the dimensional stability of experimental particleboard panels made from rubberwood (Hevea brasiliensis) using modified starch as binder. Panels were manufactured using 15% corn starch modified with glutardialdehyde and 13% modified starch with 2% Urea Formaldehyde resin as improvement. The particleboards were tested for their dimensional stability towards moisture. Results found that the 2% replacement of modified starch with urea formaldehyde resin showed a little increased in dimensional stability compared to using glutardialdehyde modified corn starch only as the binder. Therefore, this study indicated that combination of modified corn starch and urea formaldehyde resin can have a potential to be used as an improved binder to produce particleboard panels with accepted properties.Â Â